Mucosite oral e qualidade de vida e de depressão/ansiedade em pacientes com câncer do sistema digestório - Carvalho, Márcia de (2016)
The association of depression and anxiety with the development of mucositis leads to a great loss in the quality of life of patients with cancer. The aim of this study was to verify the relationship between depression / anxiety and quality of life indices with the presence of mucositis in patients undergoing treatment of cancer of the digestive system. Included in this study were patients seen at the Instituto de Cancer de Campo Mourão-PR (INCAM), with diagnosis of cancer in the digestive system. These patients underwent examinations and after diagnosis of mucositis, they answered the questionnaires HADS - Hospital Anxiety and Depression Scale for evaluation of the presence of symptoms of anxiety and depression in hospital and UW-QOL - University of Washington for quality of life evaluation. These evaluations occurred at three times: after diagnosis, during treatment and two months after the end of treatment. Student's t-tests, Mann-Whitney and Wilcoxon were used for statistical analysis. The data of the questionnaires were confronted with clinical examinations that evaluated the presence of mucositis. Mucositis was present in 86.6% of patients. After the evaluation period, there was a decrease in quality of life (p <0.005) and an increase in depression / anxiety (p <0.05). The presence of mucositis was directly related to decreased quality of life and increased levels of depression / anxiety. The results showed that quality of life, depression and anxiety and mucositis development are highly correlated in patients with cancer in the digestive system